Correlation Between Serum High-Sensitivity C-Reactive Protein, Tumor Necrosis Factor-Alpha, Serum Interleukin-6 and White Matter Integrity Before and After the Treatment of Drug-Naïve Patients With Major Depressive Disorder - Chen, Liping; Zeng, Xiangling; Zhou, Sijia; Gu, Zhiwen; Pan, Jiyang (Frontiers in Neuroscience, 2022)
Back ground: Previous studies have noticed that systemic inflammation may alter integrity of white matter. However, how the levels of serum cytokine affect the integrity of white matter of in the major depressive disorder（MDD）patients are unclear. Our study aimed to investigate the association between the inflammatory cytokine levels and white matter microstructure in drug-naïve patients with MDD pre- and post-treatment. Method: 29 MDD patients and 25 healthy controls (HC) were included. Diffusion tensor imaging (DTI) was conducted in all subjects at baseline and the MDD patients were reassessed after venlafaxine treatment, using a tract-based spatial statistics (TBSS) analysis. Morning serum interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), and high-sensitivity C-reactive protein (hs-CRP) concentrations in MDD patients also were measured pre- and post- treatment. Results: Significant reduced fractional anisotropy (FA) values in the bilateral superior fronto-occipital fasciculus (SFO), posterior limb of internal capsule (IC-PL) and fornix were found compared to the HC and FA values in these regions in MDD patients have risen to normal levels except the bilateral SFO after treatment. FA in the left IC-PL were inversely correlated with the peripheralhs-CRP levels, both pre- and post-treatment for MDD patients； Conclusions：Our results suggested that the white matter integrity in left IC-PL were significantly inversely correlated with the peripheral hs-CRP levels in both pre- and post-treatment MDD patients.